Effect of types of mind maps on writing performance across various learning styles and genders: a case study at IAIN Palangka Raya / Aisyah Hafshah Saffura El-Muslimah ... [et al.] - El-Muslimah, Aisyah Hafshah Saffura; Hartono, Rudi; Faridi, Abdurrahman; Astuti, Puji; Azman, Mohamed Nor Azhari (Universiti Teknologi MARA, 2023)
This research measured the interaction effect among learning styles, gender, and types of mind maps on writing performance at IAIN Palangka Raya, Indonesia. The design applied a posttest quasi-experiment using a 3x2x2 analysis of variance. The study involved EFL participants comprising three groups based on learning styles (x1): auditory, visual, kinaesthetic; gender (x2): male and female; model of mind map (x3): digital mind map/DMM and paper mind map/PMM. The total participants were 30 L2 learners. Result revealed that a significant interaction among learning styles (x1), gender (x2), and types of mind map (x3) exists on the learners’ writing performance at the MS 129.14, F(2.30)=3.64, p=0.04. However, no interaction effect between learning styles and gender F(2.29)=0,21, p=0.81, eta 0.02; between learning styles and types of mind map F(2.29)=0.85, p=0.44, eta 0.09; between gender and types of mind map F(1.29)=0.49, p=0.49, eta 0.03 on writing performance. The main effect also confirmed that a significant difference exists on the effect of learning styles at F(2.29)=33.65, p=0.00, eta 0.79; gender at F(1.29)=4.91, p=0.04, eta 0.32; and types of mind maps at F(1.29)=16.83, p=0.00, eta 0.48 on the learners’ writing performance. The study provided a new insight on teaching writing using mind map technique.